2018
DOI: 10.1002/adma.201804909
|View full text |Cite
|
Sign up to set email alerts
|

Gel/Solid Polymer Electrolytes Characterized by In Situ Gelation or Polymerization for Electrochemical Energy Systems

Abstract: A gel polymer electrolyte (GPE) is a liquid electrolyte (LE) entrapped by a small amount of polymer network less than several wt%, which is characterized by properties between those of liquid and solid electrolytes in terms of the ionic conductivity and physical phase. Electrolyte leakage and flammability, demerits of liquid electrolytes, can be mitigated by using GPEs in electrochemical cells. However, the contact problems between GPEs and porous electrodes are challenging because it is difficult to incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(126 citation statements)
references
References 72 publications
1
116
0
1
Order By: Relevance
“…To better understanding the above potential shifts and peak broadening, we use Galvanostatic Intermittent Titration Technique (GITT) analysis (see the Supplementary Note 2 for the detailed analysis method and raw data is provided in Further, we observed that the gel electrolyte slightly increases the overpotential compared to the liquid electrolyte, but it stabilises interfacial side reactions as will be demonstrated by long-term galvanostatic cycling (see further). 46,47 In most studies on Li metal anodes, the change in plating and stripping overpotential is reported as the cell is charged and discharged to a fixed capacity. However, because our anodes are relying on a combination of different energy storage mechanisms, we also galvanostatically cycling batteries to the following capacities: (i) lithiation capacity of Si/G with further Li plating/stripping capacity of 100 mA h g À1 denoted 'Li100/Si/G' (total capacity B600 mA h g À1 ); (ii) lithiation capacity of G (without Si coating) with a further Li plating/stripping capacity of 100 mA h g À1 denoted 'Li100/G' (total capacity B460 mA h g À1 , same amount of plating as Si/G electrodes); (iii) lithiation capacity of G (without Si coating) with a further Li plating/stripping of 240 mA h g À1 denoted 'Li240/G' (total capacity B 600 mA h g À1 , same capacity as Si/G electrodes)., All tests are performed at 300 mA g À1 for over 150 hours.…”
Section: Resultsmentioning
confidence: 99%
“…To better understanding the above potential shifts and peak broadening, we use Galvanostatic Intermittent Titration Technique (GITT) analysis (see the Supplementary Note 2 for the detailed analysis method and raw data is provided in Further, we observed that the gel electrolyte slightly increases the overpotential compared to the liquid electrolyte, but it stabilises interfacial side reactions as will be demonstrated by long-term galvanostatic cycling (see further). 46,47 In most studies on Li metal anodes, the change in plating and stripping overpotential is reported as the cell is charged and discharged to a fixed capacity. However, because our anodes are relying on a combination of different energy storage mechanisms, we also galvanostatically cycling batteries to the following capacities: (i) lithiation capacity of Si/G with further Li plating/stripping capacity of 100 mA h g À1 denoted 'Li100/Si/G' (total capacity B600 mA h g À1 ); (ii) lithiation capacity of G (without Si coating) with a further Li plating/stripping capacity of 100 mA h g À1 denoted 'Li100/G' (total capacity B460 mA h g À1 , same amount of plating as Si/G electrodes); (iii) lithiation capacity of G (without Si coating) with a further Li plating/stripping of 240 mA h g À1 denoted 'Li240/G' (total capacity B 600 mA h g À1 , same capacity as Si/G electrodes)., All tests are performed at 300 mA g À1 for over 150 hours.…”
Section: Resultsmentioning
confidence: 99%
“…6,138 Among them, liquid-phase gel polymer electrolytes are also considered to be quasi-solidstate electrolytes, and they currently dominate solid-state CS studies because of their highest ionic conductivity. 160,186,[208][209][210][211][212] Gel polymer electrolytes consist of a polymer matrix (e.g., polyvinyl alcohol (PVA)) and liquid-state electrolyte (aqueous electrolyte, organic medium, ionic liquid, etc.) or conducting salts dispersed in an aqueous/organic solvent.…”
Section: Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Instead of ex-situ methods, several approaches to prepare in situ gelation/polymerization to solve the contact issue between GPE and electrode have been suggested ( Figure 18 ). For example, Song group reported physical gelation of polymer and chemical polymerization of monomer processes and their effect on electrochemical performance [ 164 ].…”
Section: Hybridized Use Of Electrolytes and Separators: Solid And mentioning
confidence: 99%
“…( b ) Gelation via cross-linking of polymers. Reprinted with permission from [ 164 ]. Copyright (2018) John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%